Diet discontinuation policies and practices of PKU clinics in the United States. - Schuett, V E (1980)
Marked diversity in policies and practices for discontinuation of the PKU diet in the U.S. was found in a nationwide survey. Seventy-two of the 78 identified clinical centers treating PKU provided data. No clinicians are currently considering diet discontinuation at ages earlier than their present policy or practice. A definite trend toward later discontinuation of diet was identified. A few clinicians have always recommended indefinite diet continuation while many clinics have experience with children ages 9--12 who have discontinued the diet. Clinics with seven or more children off diet in this age range are significantly more likely than smaller clinics to be considering a later age for diet discontinuation. There were 151 children approximately age 10 or older, who remain on a low phenylalanine diet. These children are followed by 29 clinics, but over one-half of them are followed by five clinics which have had long-standing policies of indefinite diet continuation. Factors associated with success in long-term management are a firm clinic policy supporting continued diet treatment; frequent, supportive contacts with the family; open discussion by staff with families and establishment of a trusting relationship; teaching children to accept responsibility for diet management from an early age.